State security in Brazil: A bibliographic review (1988–2022) - DE SOUZA, Luís Antônio Francisco [UNESP]; Serra, CARLOS HENRIQUE DE AGUIAR; Soares, SÍLVIO DE AZEVEDO [UNESP]; Valério, Raphael Guazzelli (My University, 2024)
Brazil has historically employed a militarized strategy for public security, using violence as a means of social control over subordinate groups and repressing social and labor movements. The involvement of military personnel and state police in justice administration and politics reflects a distortion within the Brazilian state, which the 1988 Federal Constitution did not alleviate. Instead, since re-democratization, militarization has shifted from being an extraordinary measure to becoming the norm, representing an expansion of the state of exception. This trend has culminated in the military’s return to the political scene and the presidency. This article examines the complex relationship between the militarization of public security and the recent trend of radicalization in farright political positions. The analysis centers on the theoretical debate regarding the relationship between a state of exception and neoliberalism. The research hypothesis posits a convergence between the militarization of politics, a state of exception, and state violence, which collectively impose limits on the rights enshrined in the country’s legal system.
Keywords: militarization; neoliberalism; police violence; public security; State of exception